THE EFFECT OF DIGITAL READING PLATFORMS ON EFL STUDENTS’ READING COMPREHENSION: A QUASI-EXPERIMENTAL STUDY - Dinda Dinda; Nurdin Noni; Munir Munir; Muh Tahir (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This research aimed to investigate the effect of the ReadWorks platform as a digital reading tool on the reading comprehension skills of eleventh-grade students at SMKS YPPP Wonomulyo during the 2024/2025 academic year. The study adopted a quantitative approach utilizing a quasi-experimental design to assess the effectiveness of the intervention. The population in this study comprised 150 second-grade students majoring in Computer and Network Technology, distributed across five different classes. Using a cluster random sampling technique, two classes were selected as the research sample, resulting in a total of 64 students. These students were then equally divided into two groups: an experimental group and a control group, with 32 students in each. To collect data, a reading comprehension test—administered in the form of both pre-tests and post-tests—was used alongside a perception questionnaire to gain insight into students’ attitudes toward the platform. All quantitative data were analyzed using the Statistical Package for the Social Sciences (SPSS) version 29. The pre-test scores showed relatively equal levels of reading comprehension between the experimental group (mean = 57.03) and the control group (mean = 56.25), suggesting comparable starting points. However, after the implementation of the ReadWorks platform in the experimental group, there was a marked improvement in their post-test scores (mean = 75.94), while the control group, which did not use the platform, showed a more modest increase (mean = 70.31). The results of the independent samples t-test revealed a Sig. (2-tailed) value of 0.008, which is below the 0.05 threshold, indicating a statistically significant difference in post-test performance between the two groups. In conclusion, the ReadWorks platform can be considered a valuable and effective digital resource for improving reading comprehension outcomes and fostering more engaging learning experiences among EFL students at the secondary education level